Anatomic Revascularization of the Celiac Trunk and the Superior Mesenteric Artery - Ugurlucan, Murat; Aksakal, Nihat; Onal, Yilmaz; Oztas, Didem Melis; Alpagut, Ufuk (AORTA, 2018)
Chronic atherosclerotic mesenteric ischemia is a debilitating disorder. It may cause postprandial abdominal pain leading to severe weight loss. Patients are usually emotionally affected with major depression. The disease can be treated with open surgical and endovascular techniques and both methods have individual risks and benefits. In this report, the authors present anatomical revascularization of the superior mesenteric artery and the celiac trunk.
Keywords: atherosclerosis; mesenteric ischemia; surgical revascularization